Widening use of dexamethasone implant for the treatment of macular edema - Bonfiglio V; Reibaldi M; Fallico M; Russo A; Pizzo A; Fichera S; Rapisarda C; Macchi I; Avitabile T; Longo A (Dove Medical Press, 2017)
Vincenza Bonfiglio, Michele Reibaldi, Matteo Fallico, Andrea Russo, Alessandra Pizzo, Stefano Fichera, Carlo Rapisarda, Iacopo Macchi, Teresio Avitabile, Antonio Longo Department of Ophthalmology, University of Catania, Catania, Italy Abstract: Sustained-release intravitreal 0.7 mg dexamethasone (DEX) implant is approved in Europe for the treatment of macular edema related to diabetic retinopathy, branch retinal vein occlusion, central retinal vein occlusion, and non-infectious uveitis. The implant is formulated in a biodegradable copolymer to release the active ingredient within the vitreous chamber for up to 6 months after an intravitreal injection, allowing a prolonged interval of efficacy between injections with a good safety profile. Various other ocular pathologies with inflammatory etiopathogeneses associated with macular edema have been treated by DEX implant, including neovascular age-related macular degeneration, Irvine–Gass syndrome, vasoproliferative retinal tumors, retinal telangiectasia, Coats’ disease, radiation maculopathy, retinitis pigmentosa, and macular edema secondary to scleral buckling and pars plana vitrectomy. We undertook a review to provide a comprehensive collection of all of the diseases that benefit from the use of the sustained-release DEX implant, alone or in combination with concomitant therapies. A MEDLINE search revealed lack of randomized controlled trials related to these indications. Therefore we included and analyzed all available studies (retrospective and prospective, comparative and non-comparative, randomized and nonrandomized, single center and multicenter, and case report). There are reports in the literature of the use of DEX implant across a range of macular edema-related pathologies, with their clinical experience supporting the use of DEX implant on a case-by-case basis with the aim of improving patient outcomes in many macular pathologies. As many of the reported macular pathologies are difficult to treat, a new treatment option that has a beneficial influence on the clinical course of the disease may be useful in clinical practice. Keywords: macular edema, dexamethasone, intravitreal, implant, corticosteroids